Leadership, gender, and organization - Werhane, Patricia; Painter-Morland, Mollie (Issues in business ethics, 2011)
This text provides perspectives on the way in which gender plays a role in leadership dynamics and ethics within organizations. We are also interested in understanding how women engage in other forms of social organization, i.e. organization that goes beyond, or operates outside of formal institutions or assigned positions of authority. This text seeks to explore new theoretical models for thinking about leadership and organizational influence. Most studies of women's leadership draw on an ethics of care as characteristic of the way women lead, but as such, it tends towards essentialist gender stereotypes and does little to explain the complex systemic variables that influence the functioning of women within organizations. This book moves beyond the canon in exploring alternative paradigms for thinking about leadership and gender in organizations, and about the role women play in organization, understood here also as a verb, not just a noun. The authors draw on the literature available in systems thinking, systemic leadership, and gender theory to offer alternative perspectives for thinking about the ways women lead.The book offers invaluable theoretical perspectives and insightful narratives to graduate students and researchers who are interested in women?s leadership, gender and organization. It will be of interest to all women in leadership positions, but specifically to those interested in understanding the systemic nature of leadership. - Publisher's description.